Heteromagnetic Microelectronics Microsystems of Active Type - Ignatiev, Alexander A.; Lyashenko, Alexander V.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Heteromagnetic Microelectronics: Microsystems of Active Type, by Alexander A. Ignatiev of Saratov State University and Alexander V. Lyashenko of JSC Research Institute Tantal in Russia, offers a very detailed and specialized account of the author's research and development of heteromagnetic materials and devices. The book is based on original material from the author's programs of designing heteromagnetic microsystems. Polyvalent, multiple parameter magneto-semiconductor microsystems are described and the book reports on extensive experimental and theoretical results of research in a range of frequencies up to 1000 GHz. For the first time the direction of satisfying criteria, and burst technologies, which can make a subject of discovery, are discussed in great detail. This book is intended for post-graduate students and researchers specializing in the design and application of heteromagnetic materials and devices. Alexander A. Ignatiev is author of Magnetoelectronics of Microwaves and Extremely High Frequencies in Ferrite Films (Springer, 2009).
Experimental Investigation of the Properties of Oscillating Heteromagnetic Structures at Low, Medium, and High Power Levels -- Spectra of Regular and Noise Signals -- Properties of Structures with Ferrites of Different Magnetizations -- Control Over Energy and Spectral Characteristics -- Generalization Control Characteristics in Generative Structures -- Process Modeling in Heteromagnetic Structures -- Heteromagnetic Oscillator -- Multicircuit Model of a Multifunctional Heteromagnetic Oscillator -- Calculation of Parameters of Heteromagnetic Structures -- Calculation of Parameters of Transistors, Coupling Elements, Magnetotransistors in a Frequency Band Below 100 GHz -- Calculation of Thermal Conditions of Magnetotransistors in Continuous and Pulse Modes -- Applied Aspects -- Influence of External Factors -- Multifunctional Generation and Boosting -- Multifunctional Frequency Synthesizers -- Vector Sensors and Magnetometers with Heteromagnetic Interaction -- Low-Noise Amplifiers on Magnetotransistors Below 40 GHz -- Magnetotransistors and Their Technologies -- Nonlinear Effects in Magnetotransistors and Their Elements.
Keywords: Physics; Magnetism; Microwaves; Physics; Magnetism, Magnetic Materials; Optics and Electrodynamics; Microwaves, RF and Optical Engineering